INSULIN-LIKE GROWTH FACTOR-1, CYTOLYSIS AND CHOLESTASIS IN PATIENTS WITH NON-ALCOHOLIC FATTY LIVER DISEASE AND ITS COMBINATION WITH TYPE 2 DIABETES MELLITUS - L. V. Zhuravlyova; E. V. Ogneva (Klinicist)
Purpose. The study was designed to assess the relationship between the level of plasma concentration of insulin-like growth factor-1 (IGF-1) and indices of the functional state of the liver in patients with non-alcoholic fatty liver disease (NAFLD) and its combination with diabetes mellitus (DM) 2 types depending on the trophological status.Materials and methods. It were examined 90 patients with non-alcoholic fatty liver disease and its combination with type 2 diabetes mellitus –with normal body weight and obesity, as well as 20 healthy individuals. The study was carried out using the following methods: clinical, laboratory and instrumental (including liver biopsy).Results. It was inverse the relationship between the level of IGF-1, and the level of AST, ALT, AST/ALT, total and conjugated bilirubin, alkaline phosphatase in groups of patients with comorbid disorder. There was established the significant decrease of plasma level of IGF-1, and also impairment of liver function indices in all groups in comparison with the controls, and most pronounced changes in patients with comorbid disorders and obesity.Conclusion. The established relationships suggests that the decrease of IGF-1 may represent the presence of syndromes of cytolysis and cholestasis in patients with NAFLD, type 2 DM and obesity. In order to determination the disorder of the reparative function of the liver isrecommended to determine the level of IGF-1 in patients with combination of NAFLD and type 2 DM. Patients with the level of IGF-1 < 143,9 ± 4,92 ng/ml should refer to the risk of progression of liver function disorders.